2014
DOI: 10.1111/pedi.12242
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I and insulin-like growth factor binding protein-1 are related to cardiovascular disease biomarkers in obese adolescents

Abstract: Context Insulin-like growth factor (IGF)-I and IGF binding protein (IGFBP)-1 have been linked to cardiovascular disease (CVD) risk and pathophysiology in adults, but there are limited data in youth. Objective The aim of the study was to examine the relationship between IGF and IGFBP-1 with traditional and non-traditional CVD risk factors including inflammatory markers and body composition in an obese pediatric cohort. Design A cross-sectional study. Setting The study was carried out at a university child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…When the relationship of cardiac parameters with IGF-1 or adiponectin was explored in patients with severe obesity, Sirbu et al reported the negative association of adiponectin and the positive association of IGF-1 with the left ventricular mass (LVM) [ 95 ]. On the other hand, in obese adolescents, it has been recently reported that IGF-1 and IGFBP-1 are negatively associated with traditional CV disease biomarkers and IGFBP-1 is positively associated with adiponectin [ 96 ].…”
Section: Igf-1 and Adiponectin In Relation To Cardiovascular Diseamentioning
confidence: 99%
“…When the relationship of cardiac parameters with IGF-1 or adiponectin was explored in patients with severe obesity, Sirbu et al reported the negative association of adiponectin and the positive association of IGF-1 with the left ventricular mass (LVM) [ 95 ]. On the other hand, in obese adolescents, it has been recently reported that IGF-1 and IGFBP-1 are negatively associated with traditional CV disease biomarkers and IGFBP-1 is positively associated with adiponectin [ 96 ].…”
Section: Igf-1 and Adiponectin In Relation To Cardiovascular Diseamentioning
confidence: 99%
“…41 IGF-1 production in response to an increased number of adipocytes may play a role in the decreased output of GH observed in patients who suffer from obesity. 20,42,43 However, this decrease in the secretion of this hormone is not associated with an alteration in the speed of growth, since obese children usually have a normal or even increased height for their age; for example, in this study, the obese group was 7cm taller than children of similar age with adequate weight.…”
Section: Discussionmentioning
confidence: 52%
“…18 Circulating concentrations of this protein are high during fasting, malnutrition and both types of diabetes, and are low in overweight cases. 19,20 There is also evidence that suggests that IGFBP-1 is a useful predictive marker of CVD risk given its relationship with BMI, circulating proinsulin levels, MS, 21 IR 11,17,22 and even fatty liver. 9,16 On the other hand, IGFBP-2 is a biomarker that allows identifying IR and high CVD risk in adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In childhood, IGF-I has been connected to cardiovascular risk markers in nondiabetic obese adolescents [9], and low IGF-I levels were found in obese Chinese children with low high-density lipoprotein cholesterol (HDL-c) levels [10]. …”
Section: Introductionmentioning
confidence: 99%